1990
DOI: 10.1007/bf00554819
|View full text |Cite
|
Sign up to set email alerts
|

Temperature sensitivity as a general phenomenon in a collection of chlorophyll-deficient mutants of sweetclover (Melilotus alba)

Abstract: A collection of chlorophyll (Chl)-deficient mutants of sweetclover (Melilotus alba) with defects in eight nuclear loci were grown at 17 or 26 degrees C. Plants grown at either temperature were examined for Chl content, Chl a/b ratio, expression of the light-harvesting complex II (LHC-II) apoproteins, and protochlorophyllide (Pchlide) biosynthetic capacity. Except for the ch4 mutant, the parental strain and all mutants accumulate more Chl when grown at 26 degrees C than at 17 degrees C. The ch5 mutants, lacking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
2
11
0
1
Order By: Relevance
“…Temperature sensitivity has been postulated to be a general phenomenon in Chl-deficient mutants of sweetclover (Yang et al, 1990) and Arabidopsis (Markwell and Osterman, 1992). We postulate that the bottleneck in the Chl synthesis pathway in these mutants, seen especially early in development, could simply exaggerate the low-temperature slowdown in de novo protein synthesis (Greer et al, 1991) required for the processes of development and repair and thereby enhance the mutational effects.…”
Section: Consequences Of the Block In Chl Biosynthesis In The Mutantsmentioning
confidence: 89%
“…Temperature sensitivity has been postulated to be a general phenomenon in Chl-deficient mutants of sweetclover (Yang et al, 1990) and Arabidopsis (Markwell and Osterman, 1992). We postulate that the bottleneck in the Chl synthesis pathway in these mutants, seen especially early in development, could simply exaggerate the low-temperature slowdown in de novo protein synthesis (Greer et al, 1991) required for the processes of development and repair and thereby enhance the mutational effects.…”
Section: Consequences Of the Block In Chl Biosynthesis In The Mutantsmentioning
confidence: 89%
“…In addition, the total amount of Chl and the Chl alb ratio vary greatly in response to changes in the light environment (similar to sun and shade plants) and to changes in temperature (Yang et al, 1990;Markwell and Osterman, 1992). Concomitant light-and temperature-dependent changes in LHCs, grana stacks, and general organization of the thylakoids have also been observed, with losses in peripheral LHCs in general paralleling reductions in the size and number of grana stacks (Greene et al, 1988a(Greene et al, , 1988bKnoetzel and Simpson, 1991).…”
mentioning
confidence: 99%
“…have been identified in which the restrictive growth temperature producing the Chl-deficient phenotype is either lower or higher than the temperature producing more normal Chl content (Markwell et al, 1986;Yang et al, 1990;Markwell and Osterman, 1992). For some of the mutants such as the sweetclover ch4, the Chl deficiency is not reversed when the plant is placed at a nonrestrictive temperature (Markwell and Chelgren, 1988), whereas initial studies indicated that mutants such as the sweetclover chlO and chll will markedly green when transferred to the nonrestrictive temperature (Yang et al, 1990). In this report we will examine the phe-Plant Physiol.…”
mentioning
confidence: 99%